High population density survival of the sea urchin Diadema antillarum (Philippi 1845) to a category 5 hurricane in southern Mexican Caribbean - Jorgensen, Pablo; Espinoza-Ávalos, Julio; Bahena-Basave, Humberto (HIDROBIOLÓGICA, 2017)
The vulnerability of the sea urchin Diadema antillarum to the impact of the category 5 hurricane Dean was assessed at a back-reef area of Mahahual (Southern Mexican Caribbean). Seventy days after Dean, there was a high mean Diadema population density of 12.6 ± 4.3 (SD; from here forward) ind m2 , with a large mean individual test diameter of 59.2 ±9.8 mm. This population was comparable to a previous report for the same area, just before the landfall of Dean on 21 August 2007. Immigration of adults from deeper fore-reef sites after Dean across the reef-crest was unlikely, considering the homing behavior displayed by tagged urchins. The degree of physical alteration of the habitat indicated that Diadema may survive higher hurricane-generated disturbances than those reported in previous works. These results have strong implications on the conservation of the Mexican Caribbean coral reefs since the Diadema populations surveyed have a high grazing activity and are persistent against hurricanes impact.